The Use of Natural Phenomenon in Obtaining Pregnant Rats and Mice as Experimental Animals with The Same Gestational Ages - Teguh Wahju Sardjono; Harry Kurniawan Gondo; Rivo Yudhinata Brian Nugraha; Anisa Tiara Putri; Meyland Citra Oktri Sienty Effendy (Journal of Tropical Life Science, 2019)
Hormonal oestrus synchronization is often used to obtain the same gestational ages animal models, but it may not physiologic nor practical. This research was conducted to find out a simple method in obtaining physiologic pregnant experimental animals. We used 120 female rats and mice each, divided into 16 groups with 15 members each. They were classified according to the state of parities, pair or group mating, and synchronization of oestrous. The estrous synchronization is done by utilizing the natural phenomenon (Lee-Boot, Pheromone, and Whitten effect). All nulliparous and multiparous models then were simultaneously mated for one night in pairs (1:1) or in groups (1:5) subsequently. Pregnancy rates were noted based on the number of models delivering pups on day 19-23 post-mating. The highest pregnancy rate was noted in group of multiparous, synchronized and monogamous rats (86.7%), followed by nulliparous, synchronized and monogamous rats (73.3%) and multiparous, synchronized and monogamous mice (60%) (p<0.05). Synchronization of the estrous and monogamous mating of rats or mice had significant roles in pregnancy rates (p<0.05). To get a high number of pregnant rats or mice models, we suggest to use the multiparous, estrous synchronized and monogamous simultaneous mating within one night.